2014
DOI: 10.4236/ojst.2014.43019
|View full text |Cite
|
Sign up to set email alerts
|

The Shear Bond Strengths of Composite Bonded to Dentine Following Treatment with Two Dentine Occluding Desensitizing Toothpastes

Abstract: Aim: This study determined whether prior brushing with desensitizing toothpastes (Sensodyne Rapid Relief and Colgate Pro-Relief) affected the shear bond strengths of composite to dentine surfaces after appropriate use of two different dentine bonding agents (SingleBond and PQ-1). Materials and Methods: Sixty caries free molar teeth were cleaned, disinfected and embedded in individual cylinders of polymethylmethracyrlate. The occulsal surfaces were flattened to expose dentine and finished down with 600 grit sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
3
2
0
Order By: Relevance
“…Considering Colgate Sensitive Pro-Relief desensitizing toothpaste, our results are consistent with other studies in the literature Marchan et al, 2014;Yang et al, 2014;Canares et al, 2012), which presented that the use of this toothpaste did not affect bond strength, when compared to the control group, observing even a slight increase in the values of bond strength (Canares et al).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Considering Colgate Sensitive Pro-Relief desensitizing toothpaste, our results are consistent with other studies in the literature Marchan et al, 2014;Yang et al, 2014;Canares et al, 2012), which presented that the use of this toothpaste did not affect bond strength, when compared to the control group, observing even a slight increase in the values of bond strength (Canares et al).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, it is also acknowledged that the mineral deposits formed by the desensitizing toothpastes mentioned above are unstable (Yang et al), or not tenacious enough, to affect the formation of the hybrid layer (Marchan et al, 2014), therefore, not interfering on bond strength. Studies that used conventional bonding systems in dentin hybridization, which previously were exposed to desensitizing dentifrices, attributed their results to phosphoric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the fact that the extended use of arginine/calcium carbonate (CSPR) and calcium and sodium phosphosilicatebased (SRP) desensitizing toothpastes did not interfere significantly with bonding strength to dentin, it did influence the microhardness and roughness of the substrate. In the microshear test, considering desensitizing toothpastes, the study results agree with other studies available in the literature (15)(16)(17)(18), demonstrating that the use of these toothpastes did not affect the bonding to dentin compared to the control group and included a discrete increase in bond strength values (16).…”
Section: Discussionsupporting
confidence: 88%
“…b 15) A previous study revealed that the mineral deposits formed by calcium sodium phosphosilicate desensitizing toothpastes were unstable (62) and not strong enough to affect the formation of the hybrid layer resulting in no interference on bond strength. (63) This was in agreement with the present study which showed that there was no significant difference in microtensile bond strength of adhesive systems treated to dentin between the groups using desensitizing toothpaste containing calcium sodium phosphosilicate compared to nonbrush group in each adhesive system. Therefore, the first null hypothesis was accepted.…”
Section: Data Collection and Analysissupporting
confidence: 93%